Somatoform abdominal pain in surgery: is SD worthy of surgical attention? Case reports and literature review. (24th August 2012) - Abd Elwahab, Sami Medani; Doherty, Eva; Elsheikh, Hashim
Abstract : Somatoform disorders (SD) or medically unexplained physical symptoms (MUPS) are a group of disorders that represent a group of symptoms that cannot be explained by an organic or physical pathology. These disorders are widely prevalent, and, if unrecognised, SD may lead medical professionals to embark on tests or procedures which may inflict unnecessary iatrogenic complications. Despite the high prevalence, they are only poorly included in medical training curricula, at both undergraduate and postgraduate levels. In this article, we review the literature and present two cases. The first one presented with a recurrent acute abdomen had an unnecessary CT abdomen. The second case had laparoscopy for acute right-sided abdominal pain which turned out to be normal, and was readmitted again after a short period with acute urine retention which resolved spontaneously following discussion with the patient and family. Both cases were referred for psychiatric assessment and their family doctors were informed.